MEMAHAMI PENGEMBANGAN KOMPETENSI TENAGA KEPENDIDIKAN YANG EFEKTIF - Duki (AN NAHDLIYYAH, 2022)
The competence of a manager is one of the factors in the development of an organization. A manager who has adequate competence tends to be able to improve the organization, whereas a manager who lacks competence tends to make the organization stop or retreat. Because management controlled by managers is the center or core of administration. While administration is a process that exists within the organization. If the process is getting better, it means the organization is progressing. On the other hand, if the process gets worse and eventually stalls, it means that the organization is retreating and eventually dies. This article discusses the Competence Development of Education Personnel (Staff) and the reasons why it needs to be done. This article also discusses the obstacles faced in the effort to develop the competence of education personnel, and most importantly discusses the models of staff competency development according to experts.